Twenty-eight loci that influence serum urate levels: analysis of association with gout. Issue 1 (3rd September 2014) - Phipps-Green, A J; Merriman, M E; Topless, R; Altaf, S; Montgomery, G W; Franklin, C; Jones, G T; van Rij, A M; White, D; Stamp, L K; Dalbeth, N; Merriman, T R
Abstract : Objectives: Twenty-eight genetic loci are associated with serum urate levels in Europeans. Evidence for association with gout at most loci is absent, equivocal or not replicated. Our aim was to test the loci for association with gout meeting the American College of Rheumatology gout classification criteria in New Zealand European and Polynesian case-control sample sets. Methods: 648 European cases and 1550 controls, and 888 Polynesian (Ma¯ori and Pacific) cases and 1095 controls were genotyped. Association with gout was tested by logistic regression adjusting for age and sex. Power was adequate (>0.7) to detect effects of OR>1.3. Results: We focused on 24 loci without previous consistent evidence for association with gout. In Europeans, we detected association at seven loci, one of which was the first report of association with gout ( IGF1R ). In Polynesian, association was detected at three loci. Meta-analysis revealed association at eight loci—two had not previously been associated with gout ( PDZK1 and MAF ). In participants with higher Polynesian ancestry, there was association in an opposing direction to Europeans at PRKAG2 and HLF ( HLF is the first report of association with gout). There was obvious inconsistency of gout association at four loci ( GCKR, INHBC, SLC22A11, SLC16A9 ) that display very similar effects on urate levels. Conclusions: We provide the first evidence for association with gout at four loci ( IGF1R, PDZK1, MAF, HLF ). Understanding why there is lack of correlation between urate and gout effect sizes will be important in understanding the aetiology of gout.